2023
DOI: 10.1101/2023.08.07.552289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell somatic copy number variants in brain using different amplification methods and reference genomes

Ester Kalef-Ezra,
Zeliha Gozde Turan,
Diego Perez-Rodriguez
et al.

Abstract: The presence of somatic mutations, including copy number variants (CNVs), in the brain is well recognized. Comprehensive study requires single-cell whole genome amplification, with several methods available, prior to sequencing. We compared PicoPLEX with two recent adaptations of multiple displacement amplification (MDA): primary template-directed amplification (PTA) and droplet MDA, across 93 human brain cortical nuclei. We demonstrated different properties for each, with PTA providing the broadest amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…15 Knouse et al reported a significantly lower frequency (2.2%; 95% CI 0.3%–7.9%) for large CNAs in human brain cells 35 . More recently, Kalef-Ezra et al applied PTA to human brain cells and found 33.8% to have at least one megabase-scale CNA 36 . These discrepancies highlight the need for further research into the prevalence of CNAs in the human brain.…”
Section: Resultsmentioning
confidence: 99%
“…15 Knouse et al reported a significantly lower frequency (2.2%; 95% CI 0.3%–7.9%) for large CNAs in human brain cells 35 . More recently, Kalef-Ezra et al applied PTA to human brain cells and found 33.8% to have at least one megabase-scale CNA 36 . These discrepancies highlight the need for further research into the prevalence of CNAs in the human brain.…”
Section: Resultsmentioning
confidence: 99%